Ylide‐Functionalized Diisopropyl Phosphine (prYPhos): A Ligand for Selective Suzuki‐Miyaura Couplings of Aryl Chlorides. Issue 19 (8th June 2022) - Wei, Xiao‐Jing; Xue, Bingxiang; Handelmann, Jens; Hu, Zhiyong; Darmandeh, Heidar; Gessner, Viktoria H.; Gooßen, Lukas J.
Abstract: The ylide‐functionalized diisopropyl phosphine (prYPhos) promotes Pd‐catalyzed Suzuki‐Miyaura couplings of aryl chlorides and bromides with arylboronic acids. Using Pd2 (dba)3 /prYPhos as the catalyst and K2 CO3 as the base, various (hetero)biaryls were synthesized in 45–98% yields at mild reaction conditions, tolerating sensitive functional groups and steric hindrance. The electron rich, sterically demanding ligand induces a high selectivity for halides versus triflate. Chloroaryl triflates were selectively coupled at the chloride, leaving inherently more reactive triflate groups in place. Abstract :